2020
DOI: 10.1093/icvts/ivaa008
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle quality affects patient outcomes in acute type A aortic dissection

Abstract: OBJECTIVES Although skeletal muscle quantity is linked to surgical outcomes, quality remains unexamined. In this study, we evaluated whether skeletal muscle quality and quantity could predict surgical outcomes in acute type A aortic dissection (ATAAD). METHODS Skeletal muscle quality and quantity were evaluated using computed tomography (CT) values and the psoas muscle mass index, respectively. From May 2004 to December 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The 5-year survival was significantly worse for the group of patients with intramuscular fat (IMF) deposition (IMF 73.8% vs. non-IMF 88.2%; P = 0.010). The multivariable Cox analysis showed that IMF deposition was a statistically significant predictor of poor survival (HR = 3.26; P = 0.004), unlike PMI [63].…”
Section: Yesmentioning
confidence: 98%
“…The 5-year survival was significantly worse for the group of patients with intramuscular fat (IMF) deposition (IMF 73.8% vs. non-IMF 88.2%; P = 0.010). The multivariable Cox analysis showed that IMF deposition was a statistically significant predictor of poor survival (HR = 3.26; P = 0.004), unlike PMI [63].…”
Section: Yesmentioning
confidence: 98%
“…The criteria reported by the European Working Group on Sarcopenia in Older People (EWGSOP) can be used in diagnosing sarcopenia; however, the best method to assess sarcopenia remains a matter of debate [6,7]. It has already been reported that psoas muscle volume on abdominal computed tomography (CT) is associated with prognosis for aortic and off-pump coronary artery graft bypass and valve surgery [7][8][9][10][11] and is currently one of the most used evaluation methods. In contrast, pectoralis muscle mass has been used in predicting prognosis in case of respiratory diseases [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study of body composition, namely the study of skeletal muscle (SKM), subcutaneous (SAT), visceral (VAT) and intramuscular (IMAT) adipose tissue, has been shown to drive clinical outcomes (toxicity, survival, infection, surgery, length of hospital stay). Specifically, SKM is an important prognostic factor for various outcomes such as cancer survival Penna et al (2019) and surgical outcomes Gomibuchi et al (2020); Nishimura et al (2019). For identical height and weight, SKM mass can vary substantially and for those outcomes that depend on skeletal mass (such as chemotoxicity), accurate measurement of the individual's SKM is very critically important.…”
Section: Introductionmentioning
confidence: 99%